A Scheme for Usage Integrity - Fenna, D. (Methods of Information in Medicine, 1987)
The need for assured integrity and confidentiality in medical information systems has long been recognized and has been the subject of major international working conferences [4, 5]. Beyond the purely physical, the field of data protection is commonly recognized as being divided into data/program integrity and usage integrity. This paper addresses the latter, describing a sophisticated scheme developed at the University of Alberta and progressively implemented at several associated hospitals. The IFIP-IMIA WG4 conference of 1982 reported in its conclusions “a need for well defined and accurately described cases that can be used as a reference”; this paper offers one such case.
Keywords: Confidentiality; Data Protection; Usage Integrity